Mendamba Kebersamaan: Konsumsi Pengalaman Pertemanan di Kalangan Dewasa-Muda melalui Vakansi Terbuka Berbasis Komunitas - Aisyah, Asmi Nur (Jurnal Studi Pemuda, 2024)
This article explores how young adults navigate the challenge of spending leisure time with friends amid the increasingly individualized transition to adulthood in the era of late modernity. Heightened by productivity demands that contribute to feelings of alienation, maintaining friendships has become increasingly difficult. As a result, opportunities to experience being with friends are limited, prompting them to look for alternatives, one of which is through Community-Based Open Vacations (CBOV), known in Indonesian as Vakansi Terbuka Berbasis Komunitas (VTBK). Inspired by the resurgence of open trips following the COVID-19 pandemic, VTBK offers curated experiences of social togetherness as a means for young adults to engage in shared vacations. This research was conducted through an eight-month ethnographic study (September 2023 - April 2024) on two VTBKs as the main site, which were Sobat Healing (@kamisobathealing) and Besok Libur (@besoklibur.titik), and three other VTBKs as additional sites, which were Jalan-Jalan Jajan (@_jalanjalanjajan), Sahabat Bermain (@sahabat_bermain), and Nyari Bandung (@nyari.bandung). The results show that VTBK constructs the need for friendship among young adults through experiential consumption of being together with friends. In the process, VTBK seeks to position the relationship between participants in a strangership relation as a substitute for previously established friendships. However, these relationships can only develop into deeper friendships through socio-technical interactions on social media.